Politik Klientelisme di Pemilu Serentak 2019 - Umagapi, Juniar Laraswanda (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2021)
Money politics cannot be separated from the constellation of elections in Indonesia. There is no election without money politics in it. To get votes, all parties are competing to use all means, be it the dawn attack of money politics before the election. It is impossible for a candidate to run for office not to use a penny even because it is no longer a public secret that without having a lot of money, he cannot escape running for government representatives. Gellner & Waterbury, Patrons, and Clients in the Mediterranean Societies said money politics exists in a society that is patron-client when groups in power or certain privileges give money or other gifts in return for the loyalty of their followers (clients). This of course applies to elections in Indonesia, not only reciprocation for voting but guaranteeing the votes of citizens because the public usually remembers the giving of candidates as the time approaches the election. For this reason, there have been many dawning attacks on money politics in Indonesia. This article will describe real-world examples of money politics during the 2019 election and cases of money politics that occurred in society. The impact of money politics on democracy and future recommendations for the government.